2021
DOI: 10.3233/idt-190176
|View full text |Cite
|
Sign up to set email alerts
|

Clustering of bank customers based on lifetime value using data mining methods

Abstract: In the current competition environment, organizations have realized that to gain profit, in addition to attract customers, they should have a good relationship with them Understanding the needs of customers and providing services for them are important factors in the success or failure of any organization. Therefore, we need to a standard measure to assess the value of customers and, as a result, establish a profitable and long-term relationship with them. Customer lifetime value is a standard measure used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…Data mining techniques generally consist of three stages: data preparation, pattern finding, and result interpretation and evaluation. These three stages can be divided into seven steps, as shown in Figure 1 [11][12][13].…”
Section: Msda Analysis Based On A-amentioning
confidence: 99%
See 1 more Smart Citation
“…Data mining techniques generally consist of three stages: data preparation, pattern finding, and result interpretation and evaluation. These three stages can be divided into seven steps, as shown in Figure 1 [11][12][13].…”
Section: Msda Analysis Based On A-amentioning
confidence: 99%
“…In Equation (12), Zj indicates the comprehensive data value, and Z ij indicates the jth indicator of the ith data of a certain evaluation data. Then build the decision matrix of the evaluation object, and finally use Equation (13) to calculate the indicator weights can be.…”
Section: A Multi-level Approach To Assessing Cyber Security Posturementioning
confidence: 99%
“…e University of California, Berkeley, conducted an experiment to generate documents using the gpt-3i5j pretraining model. In the experiment, Researchers input the title and introduction of the experimental paper and generate the model and other paper contents [15].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hasheminejad & Khorrami [6] used two clustering algorithms, i.e., K-means and CPSOII, to segment customers. By analyzing the dataset, they found that, compared to K-means, the advantage of CPSOII was that it could determine the number of clusters automatically.…”
Section: Introductionmentioning
confidence: 99%